The black cauldron - Alexander, Lloyd (Alexander, Lloyd. Chronicles of Prydain., 1965)
Peace reigns in Caer Dallben, where Taran works as Assistant Pig-Keeper, but evil threatens the rest of Prydain. The diabolical Arawn's army grows every day, and his terrible warriors never die. They are born in the Black Cauldron from the stolen bodies of slain soldiers. If evil is to be defeated, the cauldron must be destroyed. Taran volunteers to travel to Arawn's stronghold and assist in the destruction of the dreaded cauldron. With his faithful friends reassembled, Taran marches off to face great danger with a courageous heart.